The duality of innovation and food development versus purely traditional foods - Guiné, Raquel P.F. (2022)
Background Intangible cultural heritage includes knowledge and skills transmitted throughout times, and this also applies to the food sector. Traditional knowledge assumes important social and economic value, which is relevant both for sectorial clusters as well as for majority social groups. Scope and approach The objective of this review was to analyse the constraints and motivations for development in the sector of traditional foods, from the point of view of marketing and consumer trends. This review was based on published works searched for in scientific databases, such as ScienceDirect, PubMed, Scopus and web of Science. Key findings and conclusions This review showed that the value of tradition, recognized in many sectors of society, is also important in the food sector, which is particularly rich in ethnical elements, local ingredients, traditional formulations and social aspects, linked not only to the food itself but also to the act of eating and sharing. However, the food industry seeks development of new products that follow modern trends and are able to conquer today's consumers, while at the same time maintaining the identity of specific products, valued as traditional.